An exploratory pilot study to assess self-perceived changes among social assistance recipients regarding employment prospects after receiving dental treatment. Issue 1 (December 2015) - Singhal, Sonica; Mamdani, Muhammad; Mitchell, Andrew; Tenenbaum, Howard; Quiñonez, Carlos
Abstract Background Strengthening self-efficacy in job-seeking among individuals with dental problems has been identified as an important factor in facilitating job procurement and maintenance. There is no knowledge about whether receiving dental treatment improves someone's self-efficacy in seeking a job. This work explores this relationship. Methods An exploratory pilot study of a convenience sample of 30 social assistance recipients of Ontario, Canada, was conducted using a pre- and post-dental treatment survey, which included both quantitative and qualitative components. The survey included two validated instruments Oral Health Impact Profile (OHIP-14) and Job-Seeking Self-efficacy scale (JSS). Changes in scores of both scales following dental treatment were calculated. Pearson correlation was performed between OHIP-14 and JSS scores. Qualitative data were transcribed and interrelated ideas were grouped together to generate themes. Results Mean scores for OHIP-14 (23.4 to 6.7, p < 0.001, effect size: 1.75) and median scores for JSS (4.9 to 5.5, p = 0.002, effect size: 0.40) changed significantly after receiving dental treatment. A significant negative correlation (−0.56, p = 0.001) was observed between OHIP-14 and JSS scores indicating that job-seeking self-efficacy improves with improvement in oral health related quality of life (OHRQoL). Qualitative analysis reveals participants' physical and psychosocial impacts of dental problems; barriers experienced in accessing dental care and seeking a job; and changes perceived after receiving dental care. Conclusion Results of our survey indicate that social assistance recipients experience negative impacts of dental problems and perceive improvements in OHRQoL and job-seeking self-efficacy after receiving dental treatment.